Perlindungan Hukum Terhadap Korban Kekerasan dalam Rumah Tangga: Telaah Atas UU No. 23 Tahun 2004 - Rasito Rasito (Harakat an-Nisa: Jurnal Studi Gender dan Anak, 2019)
This writing is aimed at investigating the Law No. 23 2004 on the elimination of violence in house hold. This law convers the prevention, protection and recovery action of the victim of violence specifically. The reinforcement of the law is still facing a bitter dilemma. The law demands that all the law enforcers and related-authorities to be responsive and sensitive toward the interest of household in which from the beginning is aimed at the unity and harmonious life of the household.